RELATIONSHIP BETWEEN OCCUPATION AND REACTIVE HBSAG TTI SCREENING IN DONORS AT THE INDONESIAN RED CROSS IN MAKASSAR CITY IN 2022-2023 - Amal, Muhammad Ikhlasul; Sri Julyani; Dirgahayu Lantara, Andi Millaty Halifah; Irmayanti; Abdul Mubdi Ardiansar Arifuddin Karim (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Hepatitis B is a major global health problem that is deadly, with the risk of transmission being through blood. Therefore, blood safety efforts are carried out by screening for Transfusion-Transmitted Infections (TTI). This study aims to analyze the relationship between occupational type and reactive TTI screening results for HBsAg in donors at the Indonesian Red Cross Blood Transfusion Unit in Makassar City in 2022–2023. This study used a cross-sectional analytical descriptive design utilizing secondary data from 665 voluntary donors whose TTI screening results were reactive to HBsAg at the Indonesian Red Cross Blood Transfusion Unit in Makassar City in the period 2022–2023. Data analysis to examine the relationship between occupational variables and reactive TTI results was performed using the Chi-Square Test. The results showed a significant relationship between occupation and reactive TTI results of HBsAg donors with a p-value of 0.018 (p < 0.05). These findings suggest that occupational type may act as a risk factor for possible exposure to or infection with the hepatitis B virus.